Efek Penambahan Probiotik terhadap Pertumbuhan Cacing dan Kualitas Kompos yang Dihasilkan - Ereminas Nirigi; Sucahyo Sucahyo; Jacob La Oktulseja (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2019)
This study aims to determine the effect of Petro Gladiator® probiotic on the growth of earthworms (Lumbricus rubellus), in terms of the length and weight of earthworms to determine the compost produced from probiotics and earthworms (Lumbricus rubellus). This study used a Completely Randomized Design (CRD) with 3 treatments and 4 replications. The sample of this study is 3 kilograms of earthworms with hand sorting. The results showed that administration of Petro Gladiator® Probiotic has a significant effect (α <0.05) on the increase in total body length of earthworms, while from the weight gain of compost in treatment of different Petro Gladiator® probiotic, there was no significant difference with the Tuket test (α = 0.05). The administration of probiotics significantly (α <0.05) increased the percentage of total N and P content, and decreased total K content. The addition of Petro Gladiator® probiotics has an effect on the length and weight of earthworms. The addition of Petro Gladiator® probiotics also improves the quality of compost, N-total, P-total, organic matter and decreases the C / N ratio. Keywords : Earthworm, compost, cow dung medium, probiotics.